INVESTIGATING THE ANTIFUNGAL POTENTIAL OF ESSENTIAL OILS FROM DIFFERENT PLANTS AGAINST BREAD MOLD CONTAMINANTS: A FAISALABAD, PAKISTAN PERSPECTIVE - IJAZ, A; NAZ, G; MAJEED, K; MUGHAL, VA; AMJAD, K; SARWAR, A; MAHMOOD, S (Biological and Clinical Sciences Research Journal, 2024)
Bread spoilage caused by molds poses a significant challenge to the bakery industry, resulting in financial losses for both producers and consumers due to microbial deterioration and waste. Traditional methods rely on chemical preservatives like propionic acid to extend bread shelf life, but there's growing consumer demand for natural alternatives. Essential oils (EOs) have garnered interest for their potential as natural preservatives, given their wide-ranging applications in food preservation and beyond. This study assessed the antifungal properties of EOs derived from Rosemary, Lemongrass, Clove, Cinnamon, Cardamom, and Garlic using agar well diffusion and micro-dilution methods. Samples of stale bread contaminated with various fungal species were tested, revealing that rosemary, clove, and cinnamon exhibited significant antifungal activity against common molds such as Mucor piriformis, Penicillium, Aspergillus, Alternaria, and Cladosporium possessing zones of inhibition ranging from 16±7 to 40±5. The mean MIC of rosemary, lemongrass, clove, and cinnamon against Mucor piriformis was 0.054, 0.032, 0.002, and 0.01µg respectively. 0.035, 0.033, 0.002, and 0.033µg were observed for A. fumigatus. Regarding A. flavus, the mean MIC values were 0.035, 0.003, 0.0023, and 0.009µg, while 0.037µg, 0.0023µg, 0.002µg, 0.022µg and 0.037µg, 0.032µg, 0.002µg, and 0.023µg were observed in P. chrysogenum and A. niger respectively. The MFC of the rosemary, lemongrass, clove, and cinnamon were: (M. piriformis: 0.016, 0.009, 0.002, and 0.004µg. A. fumigatus: 0.016, 0.0106, 0.0036, and 0.0043µg. A. flavus: 0.016, 0.014, 0.0043, and 0.0053µg. P. chrysogemum: 0.017, 0.014, 0.005, and 0.004µg. A. niger: 0.016, 0.014, 0.005, and 0.0043µg). While the tested EOs showed promising results in inhibiting fungal growth, further research is needed to fully understand their mechanisms of action and explore additional EO sources for potential application in the bakery industry.